Provocation in women's filmmaking : authorship and art cinema - Loreck, Janice, 1986- (Edinburgh University Press, 2023)
A new critical perspective on the female auteur that considers her place in the avant-garde tradition of provocation. Includes close critical analysis of eight contemporary women filmmakers and their provocative works. Provides an exploration and account of provocation as an artistic strategy in cinema. Offers a feminist interrogation of the gendering of provocation, and the provocateur, in the discourses of film criticism as a masculine mode. Critics regularly use the term provocateur to describe controversial film directors. Although most individuals who attract this term are men, there is a long and largely unexamined history of female auteurs who shock and unsettle their viewers. Provocation in Women's Filmmaking: Authorship and Art Cinema investigates how women directors participate in the tradition of provocative art cinema. Focusing on the post-millennium films of auteurs such as Lisa Aschan, Catherine Breillat, Jennifer Kent, Isabella Eklöf, Lucile Hadžihalilović, Claire Denis, Anna Biller and Athina Rachel Tsangari, this book considers the aesthetics and strategies of women's provocative filmmaking in contemporary cinema. Challenging the gendering of provocation as a hyper-masculine mode of authorship, the book uncovers an enticing and complex array of divisive works by women.